The Miracle Weight Loss in Primary Care? - Thew, Hui Zhu; Ching, Siew Mooi; Shamsuddin, Nurainul Hana; Teoh, Soo Huat (Malaysian Journal of Medicine and Health Sciences, 2022)
This case report illustrates how a primary care physician managed a 60-year-old woman with severe obesity, uncontrolled diabetes mellitus, and low self-esteem for many years. Through a primary care physician, bariatric surgery is recommended for patients with severe obesity, which is then co-managed in a tertiary hospital through a multidisciplinary team. Primary care physicians are on the front lines when treating patients with severe obesity. A number of studies have shown that primary care physicians have low success rates in counselling and managing patients with severe obesity.(1,2) There is also a debate about bariatric surgery being unsuitable for the elderly age. It is crucial to intervene early to prevent obesity progression and its complications. Clinical inertia is one factor that hinders patients with severe obesity. Therefore, it is essential to address the problem of severe obesity early and should not miss the opportunity to counsel the treatment options and refer these patients to bariatric surgery if indicated. Primary care physicians are also crucial in providing continuity of care after bariatric surgery.